Pengaruh Struktur Modal, Struktur Aset, Laba Bersih, Piutang Usaha, Likuiditas, Profitabilitas terhadap Arus Kas - Tatema Hondro; Masriani Laia; Mastaniria Nduru; Bayu Wulandari (Owner : Riset dan Jurnal Akuntansi, 2021)
The purpose of this study was to see and test whether the effect of capital structure, asset structure, net income, accounts receivable, liquidity, profitability variable to cash flows variable on the value of service companies listed on the IDX (Indonesia Stock Exchange) from 2017-2019. This research uses a method with a quantitative descriptive approach. The population obtained was 78 companies listed on the Indonesia Stock Exchange from 2017-2019. The sample used in this study was purposive sampling technique. The sample obtained was 12 companies. The data analysis used several analyzes, namely multiple linear analysis, the coefficient of determination test, the classical assumption test, the F test, and the t-test. This study shows that partially the variables of capital structure, asset structure, accounts receivable, liquidity, ROE has no effect on cash flow variables at service companies that listed on the Indonesia Stock Exchange, while the net income variable has an influence on cash flow variables at service companies listed in Indonesia Stock Exchange, and simultaneously the variables of capital structure, asset structure, net income, accounts receivable, liquidity, Return On Equity do not have an influence on cash flow variables in service companies that listed on the Indonesia Stock Exchange.